ARTISTIC PROBLEMS IN THE WORKS OF ERICH MARIA REMARK AND ULUGBEK HAMDAM (Scientific journal of the Fergana State University, 2025)
In the article, in the novels “Three Comrades” by Erich Maria Remarque and “Balance” by Ulug’bek Hamdam, the authors’ artistic skill and style, poetic thinking, form of expressing life, harmony, spiritual state, “uniqueness” and reflection of social environment and personality of the creator, problems of the era and hero, creative influence and tradition, artistic interpretation and expression issues to the two creators, problems such as the impact of war and socio-political changes are highlighted. The skill of the writers in using pictorial means to create different scenes is shown. In the works created by E.M.Remarque, expressive methods such as words, portraits, landscapes, artistic details and paints are widely used. In addition, the image of nature, the harmony of changes in it with the content of the work, ideological effectiveness, truthfulness of interpretation are clearly noticeable.Ulugbek Hamdam’s creativity was dominated by the method of effective use of details, ensuring the state of the characters, their inner world, experiences, and the impression of nature through similes. It has been studied that the hardships of the First World War on humanity and the changes in the characters in the series of the transitional period are illuminated in a realistic manner.